PW 1462 Can first aid education support public use of urgent care services? a qualitative study - Mytton, Julie; Bowen, Leah; Davies, Ben; Baxter, Helen; Booker, Matthew (Injury prevention, 2018)
BackgroundDespite a range of urgent care services being available in the UK, public attendance at Emergency Departments has increased markedly, placing a significant burden on these resources. Self-care and first aid education may reduce the need to attend urgent care services. Understanding public decision-making regarding the use of such services can inform whether educational measures are likely to be effective.ObjectivesTo understand the perspectives of service users and providers of urgent care services regarding who attends, where and when they attend, and the potential role of first aid education to influence that decision-making.MethodsWe conducted semi-structured interviews with recent users of urgent care services or their carers, ran two focus groups with past users of services, and interviewed healthcare practitioners who either work in urgent care services or refer to such services. Interviews were recorded, transcribed and analysed thematically.Findings11 service users or carers participated in interviews, and 12 in two focus groups. 23 healthcare practitioners were interviewed. Thematic analysis identified seven groups of urgent care services who may have the potential to benefit from first aid education. Recommendations included developing the content and delivery of first aid education to include management of minor injuries as well as life threatening ones, targeting education to specific groups of frequent users, supporting the public through first aid education to know where and when to access local urgent care services, and supporting ability to self-care.ConclusionsFirst aid education may have a role to play in supporting decision-making about use of urgent care services. The content and delivery of the education package would need development and subsequent evaluation. Policy implications Commissioners of urgent care services and first aid education programmes should consider first aid education as a potential intervention to support urgent care service use and reduce demand.